Taxonomy of the green filamentous algae of the family Chaetophoraceae (order Chaetophorales) in Thane District, Maharashtra, India - Samruddha Phadnis; Ganesh Iyer (International Journal of Life Sciences, 2016)
In the present communication the eight species of the filamentous green algae belonging to the family Chaetophoraceae collected from Thane district have been described. During the study, three species of the genus Stigeoclonium Kützing, two species of the genus Chaetophora F. Schrank and one species each of the genus Draparnaldia Bory, genus Gongrosira Kützing and genus Pleurastrum Chodat were recorded. Of these, the three species viz. Chaetophora tuberculosa, Gongrosira papuasica and Pleurastrum insigne have been probably recorded for the first time in India.